Transmembrane Protein ANTXR1 Regulates γ-Globin Expression by Targeting the Wnt/β-Catenin Signaling Pathway - Tingting Jin; Zhaojun Zhang; Yuanyuan Han; Di Li; Juan Liu; Minmin Jiang; Junwei Zhu; Ryo Kurita; Yukio Nakamura; Fangfang Hu; Yongjie Xu; Xiangdong Fang; et al. (Journal of Immunology Research)
Reactivation of fetal hemoglobin (HbF, α2γ2) alleviates clinical symptoms in patients with β-thalassemia and sickle cell disease, although the regulatory mechanisms of γ-globin expression have not yet been fully elucidated. Recent studies found that interfering with the expression of the membrane protein ANTXR1 gene upregulated γ-globin levels. However, the exact mechanism by which ANTXR1 regulates γ-globin levels remains unclear. Our study showed that overexpression and knockdown of ANTXR1 in K562, cord blood CD34+, and HUDEP-2 cells decreased and increased γ-globin expression, respectively. ANTXR1 regulates the reactivation of fetal hemoglobin (HbF, α2γ2) in K562, cord blood CD34+, and adult peripheral blood CD34+ cells through interaction with LRP6 to promote the nuclear entry of β-catenin and activate the Wnt/β-catenin signaling pathway. The overexpression or knockdown of ANTXR1 on γ-globin and Wnt/β-catenin signaling in K562 cells was reversed by the inhibitor XAV939 and the activator LiCl, respectively, where XAV939 inhibits the transcription of β-catenin in the Wnt pathway, but LiCl inhibits GSK3-β. We also showed that the binding ability of the rank4 site in the transcriptional regulatory region of the SOX6 gene to c-Jun was significantly increased after overexpression of ANTXR1 in K562 cells. SOX6 protein expression was increased significantly after overexpression of the c-Jun gene, indicating that the transcription factor c-Jun initiated the transcription of SOX6, thereby silencing γ-globin. Our findings may provide a new intervention target for the treatment of β-hemoglobinopathies.